The seventeenth-century literature handbook - Grossman, Marshall (Oxford, UK : Wiley-Blackwell, 2011)
The Seventeenth Century Handbook provides the undergraduate with a succinct account of the century's events, along with an exploration of the ways the literature reflected and helped shape the history of the time
Includes index
Keywords: English literature -- 17th century -- History and criticism